LITERATUR REVIEW: HAMBATAN PROGRAM PENCEGAHAN HUMAN PAPILLOMAVIRUS (HPV) DAN ANCAMAN INFEKSI HPV PADA PASANGAN: A Literature Review: Obstacles Of The Prevention Of Human Papilloma Virus (Hpv) Program And The Threat Of Hpv Infection In Partners - Ana Dyah Aliza; Kolifah Kolifah (Jurnal Ilmiah Kebidanan (Scientific Journal of Midwifery), 2022)
Human papillomavirus (HPV) is the cause of cervical cancer. However, the HPV prevention program has not been maximized. The impact of HPV infection is not only on women but also on men. The purpose of the literature review is to review HPV prevention programs and the impact of poor implementation of prevention. Literature review is carried out based on the suitability of the theme of the review and the article. Systematic literature search using database from PubMed. Then the prevention and impact of the HPV prevention program was analyzed using the keywords “Human papilovavirus”, “infection”, “impact” and “prevention” in combination with various other keywords. Of the 6 articles that met the inclusion criteria found, it was found that HPV prevention was carried out using vaccination and screening in women and men. However, there are obstacles in its implementation that can cause health impacts on women, men and fetuses.